2004
DOI: 10.1590/s0021-75572004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Sensibilização a alérgenos inalantes e alimentares em crianças brasileiras atópicas, pela determinação in vitro de IgE total e específica: Projeto Alergia (PROAL)

Abstract: Objective: To determine the frequency of sensitization to inhalant and food allergens in children seen at Brazilian allergy services.Patients and methods: Total and specific IgE serum levels to inhalant and food allergens (RAST, UniCAP ® Pharmacia) were measured in 457 children accompanied in pediatric allergy services and in 62 control children age matched. RAST equal or higher than class 1 was considered as positive (R+).Results: Frequency of R+ was significantly higher among atopics (361/457, 79%) when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…On the other hand, several studies have reported associations between SPT positivity and asthma and gastroesophageal reflux. 38 In study by Ribeiro et al, the presence of respiratory infections and asthma attacks were associated with atopic parents but not with the presence of two or more positive skin tests for allergies among the children who were studied. In addition, the presence of respiratory infections and asthma were not associated with parents who smoked or with studying at boarding school.…”
mentioning
confidence: 91%
“…On the other hand, several studies have reported associations between SPT positivity and asthma and gastroesophageal reflux. 38 In study by Ribeiro et al, the presence of respiratory infections and asthma attacks were associated with atopic parents but not with the presence of two or more positive skin tests for allergies among the children who were studied. In addition, the presence of respiratory infections and asthma were not associated with parents who smoked or with studying at boarding school.…”
mentioning
confidence: 91%
“…In our opinion, there are no grounds for the current movement, according to social networks, that all patients with CD should avoid cutaneous and inhalation exposure to wheat. Based on the frequency of sensitization to wheat in patients with CD equaled 4% in our study, it is still a lower proportion than the general population of the same country that was equal to 9.4% [25]. It is also important to note that most patients who had sensitization to wheat did not show symptoms when they did not follow GFD.…”
Section: Discussion/conclusionmentioning
confidence: 55%
“…Brazilian and Latin American studies are scarce. Two Brazilian multicentric studies evaluated WS in atopic patients and controls [24, 25]. The first one observed a frequency of 20.1% among atopic patients and 8.1% among controls [24]; the other study, 12 years later, observed an increase of these proportions, which were 23.4 and 9.4%, respectively [25].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…1 The great variability found among total IgE values shows its low specificity for allergic diseases, in addition to its not being recommended for screening, once the increase in serum levels may occur in several clinical situations. 5 Frequency of positivity of specifi c IgE for dust mites (D. pteronyssinus) was higher in the control group (34.8%), suggesting that atopy is not related to anaphylaxis associated with vaccine.…”
Section: Resultsmentioning
confidence: 87%